2017
DOI: 10.1088/1748-0221/12/03/c03076
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured targets irradiation by ns-laser for nuclear astrophysics applications: first results

Abstract: The studies discussed in this work are related to a scientific program that aims to reproduce astrophysical-plasmas in laboratory in order to better understand the nuclear processes involved in the stellar burning. An experimental campaign aiming to investigate the effects of innovative nanostructured targets based on Ni, Fe and Co nanowires on laser energy absorption in the ns time domain has been carried out at the LENS (Laser Energy for Nuclear Science) laboratory of INFN-LNS, Catania. Nanowires structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…There is excellent agreement between the measured neutron speed and the known 2. 45 MeV neutron speed at various detector locations.…”
Section: Neutron Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is excellent agreement between the measured neutron speed and the known 2. 45 MeV neutron speed at various detector locations.…”
Section: Neutron Yieldsmentioning
confidence: 99%
“…Therefore, the interaction of nanosecond (ns) lasers with solid targets is well suited to generate extreme plasma environments at energy levels higher than the normal range. At the LENS laboratory in Catania, Italy, nanowire targets made of different materials are irradiated by using an infrared laser with an intensity of 10 12 W/cm 2 , a pulse duration of 6 ns, and an energy of 2 J [44,45]. It was found that, in the nanowire form, nanostructures on the surface of the target can absorb laser energy with very high efficiency.…”
Section: Introductionmentioning
confidence: 99%